Samoan archaeology and cultural heritage : monuments and people, memory and history - Martinsson-Wallin, Helene, (Archaeopress, 2016)
The overall purpose of this book is to provide a foundation for Samoan students to become the custodians of the historical narrative based on Archaeological research.